Determinants of Dyslipidemia in Africa: A Systematic Review and Meta-Analysis - Obsa, Mohammed S.; Ataro, Getu; Awoke, Nefsu; Jemal, Bedru; Tilahun, Tamiru; Ayalew, Nugusu; Woldegeorgis, Beshada Z.; Azeze, Gedion A.; Haji, Yusuf (Frontiers in Cardiovascular Medicine, 2022)
Background Dyslipidemia is a common public health problem in Africa. It has emerged as an important cardiovascular risk factors. It has been steadily increasing due to economic growth, urbanization, and unhealthy dietary pattern. Therefore, it is important to identify determinants of dyslipidemia so as to prevent the condition and reduce its long term sequel. Methods: Combinations of search terms with Boolean operators were used to retrieve studies from PubMed, EMBASE, Cochrane Database, Cinahl, Scopus, Mednar, and Google Scholar. The methodological quality of each article was evaluated based on the 2017 Joanna Briggs Institute (JBI) Critical Appraisal checklist for prevalence studies. After evaluation of each study against these criteria, studies with a minimum score of 7 or above out of 9 JBI checklists were included. We included only articles presented in English language. The Cochrane Q test was used to assess heterogeneity across studies. The visual assessment of publication bias was done by creating a funnel plot. The possible causes of heterogeneity were explored by subgroup analyses. Egger’s weighted regression test was used to assess the presence of publication bias. Statistical analyses were done by STATA software version 14. Result: A total of 24 articles involving 37902 participants from 10 African countries were included. By conducting this study, we found that the overall pooled prevalence of dyslipidemia was 52.8 (95% CI 40.8 – 64.9). Individuals with a body mass index (BMI) greater than 25.0 kg/m2) and waist circumference (WC) > 94 cm were respectively 2. (95% CI ( (1.33 – 4.18), P < 0.001) and 2.33 (95% CI ( (0.75 – .29) P < 0.001) times more likely to develop dyslipidemia than those with lower values. Furthermore, patients with diabetes mellitus and hypertension were 2.32 (95% CI ( (0.89 – 6.05) P < 0.001) and 2.05 (95% CI (1.31 – 3.21), P < 0.001) times more likely to present with dyslipidemia than non-diabetic patients and those without hypertension. Conclusion: This study revealed that the prevalence of dyslipidemia is higher among study participants in African countries. Therefore, there should be a pressing public health measure to prevent, identify, and treat dyslipidemia.